Cardiovascular disorders in hemodialysis - Ronco, Claudio 1951-; Brendolan, Alessandra; Levin, Nathan W. (Karger, 2005)
Hemodialysis therapy has become a well-established form of renal replacement, and due to continuous improvements in technology, a series of new biomaterials and techniques for the clinical routine have been developed. Nevertheless, cardiovascular disorders in hemodialysis and uremia represent one of the most important aspects of modern nephrological care. This publication is therefore dedicated to cardiovascular risk factors, the role of the endothelium, problems related to mineral disorders and finally to the possible impact of new technologies on the final outcome in hemodialysis. Being a state-of-the-art appraisal of today’s technology and current issues in hemodialysis with special regard to cardiovascular disorders and risk factors, this book is a synthesis between an educational effort aimed at the newer generations of physicians and nurses in the field of hemodialysis and a state-of-the-art description of the most advanced technologies in this field. At the same time, the lessons learned from large international trials, either already completed or to be completed in the years to come, are presented
14th International Course on Hemodialysis, Vicenza, May 2005
Keywords: Nephrology; Cardiovascular System; Biochemistry; Dialysis; Medical Engineering; Komplikation; Hämodialyse; Kardiovaskuläre Krankheit; Aufsatzsammlung